2018
DOI: 10.3389/fnins.2018.00562
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Regulation of GABA Amygdala System and Relevance to Neuropsychiatric Diseases

Abstract: The amygdala is an almond-shaped nucleus located deep and medially within the temporal lobe and is thought to play a crucial role in the regulation of emotional processes. GABAergic neurotransmission inhibits the amygdala and prevents us from generating inappropriate emotional and behavioral responses. Stress may cause the reduction of the GABAergic interneuronal network and the development of neuropsychological diseases. In this review, we summarize the recent evidence investigating the possible mechanisms un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 114 publications
1
56
0
3
Order By: Relevance
“…As a consequence, a misbalance between inhibitory and excitatory synaptic input is discussed to lead to neuropsychiatric disorders (Liu et al, ). In line with this observation, excessive stress harms the neuronal network in the amygdala by GABAergic neurotransmission, which leads to inappropriate emotional and behavioral responses (Jie et al, ), whereas the progesterone derivate allopregnanolone directly inhibits GABA receptors, and thus improves cognitive balance (Locci and Pinna, ). In the PNS, activation of GABA receptors by progesterone also leads to an increased cell proliferation of aged Schwann cells (Melcangi et al, , ).…”
Section: Progesterone and Prsmentioning
confidence: 90%
“…As a consequence, a misbalance between inhibitory and excitatory synaptic input is discussed to lead to neuropsychiatric disorders (Liu et al, ). In line with this observation, excessive stress harms the neuronal network in the amygdala by GABAergic neurotransmission, which leads to inappropriate emotional and behavioral responses (Jie et al, ), whereas the progesterone derivate allopregnanolone directly inhibits GABA receptors, and thus improves cognitive balance (Locci and Pinna, ). In the PNS, activation of GABA receptors by progesterone also leads to an increased cell proliferation of aged Schwann cells (Melcangi et al, , ).…”
Section: Progesterone and Prsmentioning
confidence: 90%
“…CRF neurons in the hypothalamus are under tonic GABAergic inhibition. The link between GABA and chronic stress is well summarized by a recent review, although the emphasis was on neuropsychiatric disease (Jie et al, 2018). Thus, we contend that chronic stress may downregulate GABA inhibition of amygdala and hypothalamic pathways leading to hypertension.…”
Section: Role Of Amygdalo-hypothalamic Pathwaysmentioning
confidence: 95%
“…9 Exposure to acute or chronic stress can induce morphological and functional changes in the amygdala and these changes play an important role in stress-induced neuropsychiatric disorders. 10,11 Animal studies have revealed that stress influences synaptic plasticity, morphological remodeling, neurotoxicity, and neurogenesis in the brain and all these stress-derived physiological effects can potentially influence cognitive functions. 12,13 Adolescent stress increases anxiety behavior, 14 remodels corticolimbic structure, 15 and alters neural gene expression in adulthood.…”
Section: Introductionmentioning
confidence: 99%